2020
DOI: 10.1002/lpor.202000180
|View full text |Cite
|
Sign up to set email alerts
|

Metasurface‐Enhanced Lab‐on‐Fiber Biosensors

Abstract: The integration of metasurfaces on the tip of optical fibers enables advanced wavefront manipulations in Lab‐on‐Fiber application scenarios, and brings about new degrees of freedom that can be exploited for optimizing the surface sensitivity to local variations of the refractive index. Here, a novel biosensing platform is reported based on the integration of a phase‐gradient plasmonic metasurface on the tip of an optical fiber, able to detect biomolecular interactions with very high sensitivity. Specifically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 68 publications
0
59
0
Order By: Relevance
“…The authors have compared the sur-386 face sensitivity of phase-gradient metasurface and gradient-free one by observing the 387 plasmonic resonance wavelength shift of nanoholes under the same local refractive index 388 environment, and the experimental results have shown that the phase-gradient metasur-389 face features a higher surface sensitivity, indicated by a larger wavelength shift and en-390 hanced local field enhancement. The enhanced surface sensitivity of phase gradient fiber 391 metasurface was further demonstrated by the real-time and high-sensitivity monitoring 392 of biological molecules (Streptavidin ~a few ng/mL) [65]. 398 By implementation of real-time biological experiments, the phase-gradient fiber 399 meta-tip is capable of detecting the slight concentration change of Biotin and Biotin-Strep-400 tavidin interaction, evidenced by a larger resonance wavelength shift (Figure 9c).…”
Section: Function Of Biological Sensing and Imagingmentioning
confidence: 96%
“…The authors have compared the sur-386 face sensitivity of phase-gradient metasurface and gradient-free one by observing the 387 plasmonic resonance wavelength shift of nanoholes under the same local refractive index 388 environment, and the experimental results have shown that the phase-gradient metasur-389 face features a higher surface sensitivity, indicated by a larger wavelength shift and en-390 hanced local field enhancement. The enhanced surface sensitivity of phase gradient fiber 391 metasurface was further demonstrated by the real-time and high-sensitivity monitoring 392 of biological molecules (Streptavidin ~a few ng/mL) [65]. 398 By implementation of real-time biological experiments, the phase-gradient fiber 399 meta-tip is capable of detecting the slight concentration change of Biotin and Biotin-Strep-400 tavidin interaction, evidenced by a larger resonance wavelength shift (Figure 9c).…”
Section: Function Of Biological Sensing and Imagingmentioning
confidence: 96%
“…The probes showed a detection limit of R6G of 10 −7 mol∕L, while the enhancement factor was measured as 1300, which was then applied for rapid SERS detection of live Escherichia coli cells with Raman integration time ranging from milliseconds to seconds. Consales et al 257 used phase-gradient plasmonic MS on the optical fiber tip to detect biomolecular interactions with a limit of detection of the order of a few ng mL −1 . Beam shaping and operation.…”
Section: D Functional Surfacesmentioning
confidence: 99%
“…Compared with the traditional methods of biomedical detections, such as Enzyme-linked immunosorbent assay (ELISA), polymerase chain reaction (PCR), and fluorescence probe-based detection, etc. [ 19 , 20 , 21 ], SPR has the advantages of being label-free, having a high sensitivity, and real-time dynamic monitoring [ 22 , 23 , 24 ]. According to different excitation ways, the optical coupling mechanisms of SPR biosensing can be further classified into three categories, namely, prism-based coupling, plasmonic waveguide, and metasurfaces coupling [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%